2019
DOI: 10.3390/app9132685
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Copper-Contaminated Marginal Land for the Cultivation of Vetiver Grass (Chrysopogon zizanioides) as a Lignocellulosic Feedstock and its Impact on Downstream Bioethanol Production

Abstract: Metal-contaminated soil could be sustainably used for biofuel feedstock production if the harvested biomass is amenable to bioethanol production. A 60-day greenhouse experiment was performed to evaluate (1) the potential of vetiver grass to phytostabilize soil contaminated with copper (Cu), and (2) the impact of Cu exposure on its lignocellulosic composition and downstream bioethanol production. Dilute acid pretreatment, enzymatic hydrolysis, and fermentation parameters were optimized sequentially for vetiver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…Trees growing at brownfield and landfill sites can exhibit higher lignin content than those cultivated in uncontaminated soils due to abiotic stresses, e.g., drought-stress, leading to lower glucose yield (Edgar et al, 2021). In contrast, vetiver plants exposed to Cu excess can display a decrease in lignin and an increase in hemicellulose and cellulose contents, leading to a higher production rate of bioethanol (Geiger et al, 2019).…”
Section: Phytomanagement Benefits and Constraints-brief Overviewmentioning
confidence: 99%
“…Trees growing at brownfield and landfill sites can exhibit higher lignin content than those cultivated in uncontaminated soils due to abiotic stresses, e.g., drought-stress, leading to lower glucose yield (Edgar et al, 2021). In contrast, vetiver plants exposed to Cu excess can display a decrease in lignin and an increase in hemicellulose and cellulose contents, leading to a higher production rate of bioethanol (Geiger et al, 2019).…”
Section: Phytomanagement Benefits and Constraints-brief Overviewmentioning
confidence: 99%
“…The fermentation efficiency of the heavy metal containing biomass was higher than the control biomass. Geiger et al (2019) indicated that hydrolysates produced from Cu exposed biomass achieved a significantly greater ethanol yield and volumetric productivity compared to those of the control biomass. Wu et al (2020) also showed that the Cd-accumulated biomass showed greatly enhanced enzymatic saccharification and bioethanol production by significantly increasing cellulose accessibility and lignocellulose porosity.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have shown that the biomass harvested after phytoremediation could be utilized for bioethanol production (Ko et al 2017;Geiger et al 2019;Wu et al 2020). Ko et al (2017) found that the enzymatic hydrolysis efficiency for Zn-polluted biomass was 90% of the unpolluted biomass, while it was 77% for Cd, and approximately the same for Cr.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are many studies on soil contamination, mainly about remediation methods, such as thermal desorption, chemical oxidation, phytoremediation etc. [19][20][21][22][23][24][25], assessment of contaminated soil [26], the process of soil contamination [27], areas for contaminated soil remediation, etc. [28].…”
Section: Introductionmentioning
confidence: 99%